EXAMPLE OF CALCULATION OF REINFORCED CONCRETE BEAM SPANS FOR TEMPORARY (A-14 AND NK-100) AND PERMANENT - Radjabov Toxir Yusupovich; Ergashev Akbar Turg’unboyevich; Mirzaolimov Ilhomjon Yusufjonovich; Abdulaziz Karshiboev Ikhtior Ugli (International Journal of Innovations in Engineering Research and Technology, 2022)
An example of the computation of reinforced concrete beam spans for calculated temporary (A-14 and NK-100) and permanent loads was given in the article. Bridges are built to withstand a variety of loads, each of which consists of a mix of permanent and live loads.